Cell origin and genome profile difference of penoscrotum invasive extramammary Paget disease compared with its in situ counterpart - Rao, Yamin; Zhu, Jinchao; Zheng, Haiyan; Ren, Yong; Ji, Tianhai (Frontiers in Oncology, 2022)
Penoscrotum Extramammary Paget disease (pEMPD) is a cutaneous carcinoma with an unknown cell origin and high recurrence risk. pEMPD always presents as a in situ tumor, while some of them progress into invasive forms with more aggressive behavior. The in situ and invasive cases display different morphologies and biological behavior, and thus far a relationship between these two components has not been demonstrated. Immunohistochemistry was used to disclose the immunotype of pEMPD, the results revealed invasive/in situ possessed with some similar immunophenotypes, while invasive pEMPD showed increased expression of AR, with deceased MUC5CA expression. In all, invasive/in situ pairs demonstrate clonal relatedness which suggested an epidermal sweat gland in epiderma origin of pEMPD, the shift to invasive phenotype is associated with gain of AR protein expression, decrease in MUC5CA expression.To better understand the relationship between these distinct tumor forms, we evaluated 6 pairs of invasive/in situ pEMPD for overlapping genomic alterations by WES. The results showed that missense mutation was the predominant mutation type, and C>T transition accounted for 65.1% in all SNP mutation. Through paired analysis, we acquired top 20 differential genes. MUC4 (1 missense,1 in frame del, 1 multi hit), AHNAK2 (2 missense, 1 multi hit), DOT1L (2 missense, 1 multi hit), FRG1 (2 missense, 1 multi hit) mutations were enriched in invasive pEMPD. And these genes may play roles in the disease progression.